Hubungan Interaksi Siswa-Guru di Sekolah dengan Motivasi Belajar Siswa SMA Pertiwi 1 Padang - Aldi, Rahmat; Aulia, Farah (Lembaga Yasin AlSys, 2025)
Motivation is an internal drive that compels an individual to take action and maintain behavior consistently. This study aims to reveal the relationship between student-teacher interaction and the learning motivation of twelfth-grade students at SMA Pertiwi 1 Padang. A descriptive quantitative approach was used, with convenience sampling involving 84 students as subjects. The instruments employed were a learning motivation scale developed by Hamzah (2011) and a student-teacher interaction scale adapted from the Questionnaire Teacher Interaction (QTI). Data were analyzed using Pearson’s Product Moment correlation technique. The results show that there is no significant relationship between student-teacher interaction and students’ learning motivation. The correlation coefficient was 0.183 for positive interaction and 0.166 for negative interaction, indicating that neither form of interaction had a significant impact on students' learning motivation. These findings suggest that students’ responses to teacher interaction were suboptimal, and other factors beyond student-teacher interaction are more influential in shaping learning motivation. The conclusion of this study is that although student-teacher interaction is an important component of the learning process, in this context, it has not significantly driven learning motivation. The implication of this research is the need to evaluate the interaction approaches used by teachers and to explore other factors that more broadly influence student motivation.